The Protective Role of Enalapril on Kidney Functions in Fructose Induced Metabolic Syndrome in Rats - Orhan, Bedrettin; Gencoglu, Hasan; Üçer, Özlem; İlhan, Necip; Şahin, Kazım; Dogukan, Ayhan (My University, 2024)
Metabolic syndrome is an entity characterized by insulin resistance, hyperinsulinemia, hypertension, dyslipidemia, and obesity. In experimental models of fructose-induced metabolic syndrome, hypertension, hypertriglyceridemia, and insulin resistance were seen in rats. Enalapril, an angiotensin-converting enzyme inhibitor, inhibits the enzyme dipeptidyl carboxypeptidase, which hydrolyes angiotensin-I. This study aims to determine the potential protective roles of enalapril on kidney functions, plasma lipid levels, and some intracellular pathway markers in an experimental model of metabolic syndrome induced by fructose in rats. 28 Wistar albino male rats (8 weeks old) were included in this study, and they were divided into four equal groups. Rats were sacrificed after eight weeks. Blood samples were taken for kidney and liver function tests and lipid levels; kidney tissue samples were collected for Western blot analysis. Transforming growth factor beta (TGF-?), tumor necrosis factor-alpha (TNF-?), nuclear factor kappa B (NF-?B), interleukin-6 (IL-6), and mothers against decapentaplegic-3 (SMAD-3) protein levels were quantified by Western blotting. Administration of enalapril on high fructose-fed rats showed significant improvement in serum glucose, total cholesterol (TC), low density lipoprotien (LDL), triglyceride, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and creatinine levels but did not affect high density lipoprotein (HDL) and blood urea nitrogen (BUN) parameters. Administration of enalapril on high fructose-fed rats caused a decrease in TGF-?, IL-6, and SMAD-3 protein levels but did not affect NF-?B, TNF-?. In conclusion, feeding with high fructose causes aggravative and destructive effects on kidney and liver function tests, but enalapril administration showed significant improvement in these parameters.
Keywords: Rat; Fructose; enalapril